Experimental Determination of Optimal Conditions for Reactive Coupling of Biodiesel Production With in situ Glycerol Carbonate Formation in a Triglyceride Transesterification Process - Al-Saadi, Luma Sh.; Eze, Valentine C.; Harvey, Adam P. (Frontiers in Chemistry, 2018)
This study investigated a reactive coupling to determine the optimal conditions for transesterification of rapeseed oil (RSO) to fatty acid methyl ester (FAME) and glycerol carbonate (GLC) in a one-step process, and at operating conditions which are compatible with current biodiesel industry. The reactive coupling process was studied by transesterification of RSO with various molar ratios of both methanol and dimethyl carbonate (DMC), using triazabicyclodecene (TBD) guanidine catalyst and reaction temperatures of 50 – 80 °C. The optimal reaction conditions obtained, using a Design of Experiments approach, were a 2:1 methanol-to-RSO molar ratio and 3:1 DMC -to-RSO molar ratio at 60 °C. The FAME and GLC conversions at the optimal conditions were 98.0 ± 1.5% and 90.1 ± 2.2% respectively, after 1h reaction time using the TBD guanidine catalyst. Increase in the DMC-to-RSO molar ratio from 3:1 to 6:1 slightly improved the GLC conversion to 94.1 ± 2.8% after 2 h, but this did not enhance the FAME conversion. Methanol substantially improved both FAME and GLC conversions at 1:1 – 2:1 methanol-to-RSO molar ratios and enhanced the GLC separation from the reaction mixture. It was observed that higher methanol molar ratios (> 3:1) enhanced only FAME yields and resulted in lower GLC conversions due to reaction equilibrium limitations. At a 6:1 methanol-to-RSO molar ratio, 98.4% FAME and 73.3% GLC yields were obtained at 3:1 DMC-to-RSO molar ratio and 60 °C. This study demonstrates that formation of low value crude glycerol can be reduced by over 90% compared to conventional biodiesel production, with significant conversion to GLC, a far more valuable product.